2017
DOI: 10.1039/c6nr09368j
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the orientations of h-BN during growth on transition metals by chemical vapor deposition

Abstract: Hexagonal boron nitride (h-BN) is crucial for many applications, and its synthesis over a large area with high quality is strongly desired. A promising approach to synthesize h-BN is chemical vapor deposition on transition metal catalysts, in which the alignments of BN clusters in the initial growth determine both the types and the amounts of defects in h-BN. In the search for a better catalyst, we systematically studied the interactions between h-BN clusters and various metal surfaces. Our results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 54 publications
3
48
0
Order By: Relevance
“…The preferential registrations reflect the electron affinity of the B and N atoms, which leads to attractive (repulsive) Coulomb interactions between N (B) atoms and the first-layer Cu atoms, and hence affects the structural stability. We find that the lowest-energy structures for 0° (NIBIII) and 60° (NIBII) orientations exhibit only an energy difference ~0.05 eV, significantly smaller than the thermal energy kBT at the growth temperature (~0.1eV), indicating that the plane-toplane registry is insufficient to achieve mono-oriented growth, in agreement with reported simulations (13).…”
supporting
confidence: 91%
“…The preferential registrations reflect the electron affinity of the B and N atoms, which leads to attractive (repulsive) Coulomb interactions between N (B) atoms and the first-layer Cu atoms, and hence affects the structural stability. We find that the lowest-energy structures for 0° (NIBIII) and 60° (NIBII) orientations exhibit only an energy difference ~0.05 eV, significantly smaller than the thermal energy kBT at the growth temperature (~0.1eV), indicating that the plane-toplane registry is insufficient to achieve mono-oriented growth, in agreement with reported simulations (13).…”
supporting
confidence: 91%
“…Zhao et al investigated the alignments of triangular h-BN clusters on the (111) surface of FCC metals and the (0001) surface of hexagonal close packed (HCP) metals, respectively (Fig. 70b-e) 1665 . It is revealed that, due to equivalence of ABC… and BCA… configurations of the neighboring terraces of a vicinal FCC(111) surface, h-BN islands tend to align parallelly on neighboring terraces of a vicinal FCC(111) surface.…”
Section: Growth Mechanism Of 2d Materials Via Bottomup Synthesismentioning
confidence: 99%
“…Several theoretical studies have revealed the growth behaviours of 2D materials including both free-standing and metal-supported graphene 37–41 and h-BN. 42–46 To the best of our knowledge, there is no detailed work revealing the growth mechanism of β-G15 films.…”
Section: Introductionmentioning
confidence: 99%